2016
DOI: 10.1152/japplphysiol.00797.2015
|View full text |Cite
|
Sign up to set email alerts
|

Using devices to upregulate nonnutritive swallowing in typically developing infants

Abstract: The role of various sensory stimuli for stimulating swallowing in infants may be of importance for assisting infants to develop oral feeding. We evaluated the swallowing mechanism response to two devices for increasing the rate of nonnutritive swallowing in two typically developing infant age groups, ages 2-4 mo and 7-9 mo. One device was a pacifier familiar to the infant; the other was a small vibrator placed on the skin overlying the thyroid cartilage. The rate of nonnutritive swallowing while infants were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…18 Although there are recent studies emerging in stimulation and upregulation of swallowing, most products and protocols remain in the research development phases. 19,20 Presently, there are few management pathways that have adequate empirical evidence to inform practitioners serving children. 21 For these reasons, employing approved state or district guidelines for swallowing and feeding services in the schools is advised.…”
Section: State Of the Science: Dysphagia Intervention In The Schoolsmentioning
confidence: 99%
“…18 Although there are recent studies emerging in stimulation and upregulation of swallowing, most products and protocols remain in the research development phases. 19,20 Presently, there are few management pathways that have adequate empirical evidence to inform practitioners serving children. 21 For these reasons, employing approved state or district guidelines for swallowing and feeding services in the schools is advised.…”
Section: State Of the Science: Dysphagia Intervention In The Schoolsmentioning
confidence: 99%
“…However, this approach requires an apparatus in the mouth for air puff stimulation, which can interfere with oral intake for feeding. A recent study indicated that surface vibration to the neck significantly increased the rate of swallowing in healthy infants without significant alterations in respiration (Hegyi Szynkiewicz et al 2016). This method of noninvasive vibratory stimulation on the neck would not interfere with oral intake and thus may be suitable for dysphagia management.…”
mentioning
confidence: 99%